PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PT.BANK SULUT GO (Studi Pada Bank Sulut-Go Cabang Kawangkoan) - MANAWAN, RIDHO V.; Pio, Riane J.; Tumbel, Tinneke M. (Sam Ratulangi University, 2017)
Bank SulutGo is the Regional Bank of North Sulawesi which has a very influential impacton the sustainability of the economy in North Sulawesi, especially in the Government andInstitutional or Community Institutions of Bank SulutGo's vision is 'To become aprofessional banking services company and grow in a healthy way'.Transformational leadership is the process by which people engage with others, and createrelationships that enhance motivation and morality in leaders and followers. This type ofleader has an interest in the needs and motivation of followers, and tries to help followersachieve their best potential.Collection data is done by spreading the research instrument, the questionnaire thatcontains questions to measure Transformational Leadership and Employee Performance.The collected data is further processed by using simple linear regression analysisBased on the formulation of the problem, the purpose of this study is '' to know the effect oftransformational leadership on employee performance on the bank sulut Go KawangkoanBranch ''Results of data processing shows that there is a significant positive effect given byTransformational Leadership on Employee Performance PT.Bank SulutGo KawangkoanBranch. Thus the higher the Transformational Leadership of PT Bank Sulut GoKawangkoan Branch hence the higher level of Employee Performance in the company.Statistically proved that Transformational Leadership positively influence on EmployeePerformance so that hypothesis accepted.From the results of this study indicates Transformational Leadership is neededsomeone to stimulate employees to work better and make employees as the most valuableasset in the company. For employees, having a leader who is able to transform inleadership leads employees to be motivated and keans to work well for the company'sprogress.this shows the hypothesis of Transformational Leadership on Employee Performance ispositiveKeywords: Transformational Leadership, Employee Performance